Analyzing the system of factors influencing buying and consumption behavior and consumer behavior - GUZUN Stela (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
Highlighting the dimensions of consumer behavior definitely leads us to the conclusion that people, in different situations, but also as consumers, do not act mechanically. The different life experiences and the existing differences between consumers (generated by sex, age, occupation, profession, living environment, etc.) lead to various ways of manifesting these experiences, respectively to individual behaviors of the bearers of the demand for consumption.